THE ROLE OF PRICE AND LOCATION ON CUSTOMER SATISFACTION IN GRIYA SUTERA BALARAJA HOUSING - Andi Hasryningsih Asfar; Icin Quraysin; Ika Pratiwi; Martinus Tukiran (International Journal of Economy, Education and Entrepreneurship, 2022)
Housing is a significant need for society. All products developers offer to consumers must be oriented to consumer needs. One factor that is often considered by consumers when buying a house is price. Companies must determine the right price to target consumers interested in purchasing the marketed products. Currently, the price is still occupying the top spot. Location is also essential because a strategic location will make consumers feel comfortable. With a reasonable price and location, it is hoped that consumers will be satisfied with the products they buy. This study examines the partial effect of cost, location's partial impact on customer satisfaction, and their simultaneous effect on customer satisfaction at Griya Sutera Balaraja Housing. The population in this study was 110 heads of families, with a total sample of 55 charges of families. The results showed that the price variable based on the results of the t-test obtained a t-count value of 3.564 > t table (2.007), the results of the location t-test got a t-count value of 5.899 > t table 2.007, and the F test results obtained an F count value of 46.893 > F table 3.17. It means that partially and simultaneously, price and location affect consumer satisfaction